Studi Tiru dan Pembinaan UMKM di Kuala Lumpur Malaysia Bersama Koperasi Unit Desa Bangun Bonai Lestari - Anuar, Saiful; Iskandar, Iskandar; Yapentra, Arhipen; Aqsa, Muh. Ali; Bishry, Hasanul; Kurniawan, Teuku Reza; Fakhri, Rizqi (Penerbit Widina, Widina Media Utama, 2025)
This study aims to examine and identify the impact of the study program and coaching conducted by STIE Riau in collaboration with the Bangun Bonai Lestari Village Cooperative Unit in Kuala Lumpur, Malaysia. This program focuses on the development of Micro, Small, and Medium Enterprises (MSMEs) based on the coaching model that has been implemented in Kuala Lumpur. This study uses a qualitative approach with interviews and observations as data collection methods. The results of the study indicate that the study program and coaching of MSMEs has succeeded in increasing the capacity of local entrepreneurs in terms of managerial and technology utilization. In addition, this cross-country collaboration also shows the importance of support from cooperatives in optimizing the potential of MSMEs. This study suggests that similar programs be expanded with an emphasis on digital marketing aspects and better financial management.ABSTRAKPenelitian ini bertujuan untuk mengkaji dan mengidentifikasi dampak dari program studi tiru dan pembinaan yang dilakukan oleh STIE Riau bekerja sama dengan Koperasi Unit Desa Bangun Bonai Lestari di Kuala Lumpur, Malaysia. Program ini difokuskan pada pengembangan Usaha Mikro, Kecil, dan Menengah (UMKM) dengan berbasis pada model pembinaan yang sudah diterapkan di Kuala Lumpur. Penelitian ini menggunakan pendekatan kualitatif dengan wawancara dan observasi sebagai metode pengumpulan data. Hasil penelitian menunjukkan bahwa program studi tiru dan pembinaan UMKM berhasil meningkatkan kapasitas pengusaha lokal dalam hal manajerial dan pemanfaatan teknologi. Selain itu, kerjasama lintas negara ini juga menunjukkan pentingnya dukungan dari koperasi dalam mengoptimalkan potensi UMKM. Penelitian ini menyarankan agar program serupa diperluas dengan penekanan pada aspek pemasaran digital dan pengelolaan keuangan yang lebih baik.